Desenvolver a autonomia das crianças em idade pré-escolar - Freitas, Ana Cristina (2017)
This work was elaborated in the context of the curricular unit “Supervised Practice in Pedagogics” leading to the Master degree in Qualifying for Pre-Schooling and First Grade Teaching. The development of autonomy in pre-schooled children and the implementation of daily routines constitutes the subject of this study. A daily routine is a sequence of tasks and/or daily contextualized occurrences in the child’s learning process that contributes for an increased autonomy. Knowing what is about to follow enables the child to acquire skills for the upcoming tasks, allowing gains of self-confidence and thus building up autonomy and independence. The methodological choices of this study covered qualitative and exploratory approaches in order to pursue the intended goals: to understand how the autonomy of children can be incentivized within a pre-schooling educational institution through the pedagogic intervention of two kindergarten teachers; to identify parents' perceptions on their children autonomy regarding daily routines similar to what they have in school. Data was collect from 2 preschool teachers and from parents (N =60) using, respectively, semi-structured interviews and a survey, with a questionnaire especially designed for this work. Content analysis revealed that preschool teachers take clear preference on pedagogic differentiation as an acting principle to enhance the children’s autonomy. The house rules in each classroom and every day routine were pointed out as essential factors for the gradual improvement of autonomy. Regarding parents or guardians, the survey results indicate special highlight in autonomy regarding Sleeping Time and mainly Hygiene and Meals within the family environment. These results are consistent with the view expressed by several authors in specialized literature, who emphasize the importance of foreseeable and stable routines where Hygiene and Meals are concerned, both for the development and learning process. As perceived by parents, the autonomy is less visible in different routines, notably Dressing and Tidiness. The scale we designed and used is a contribution to acknowledge and measure the parents’ perception, although its’ psychometric qualities still require improvement. Therefore, we suggest that further studies should improve the scale with an enlarged scope of analysis.